The impact of paclitaxel and carboplatin chemotherapy on the autonomous nervous system of patients with ovarian cancer. Issue 1 (December 2016) - Dermitzakis, Emmanouil; Kimiskidis, Vasilios; Lazaridis, George; Alexopoulou, Zoi; Timotheadou, Eleni; Papanikolaou, Alexandros; Romanidou, Ourania; Georgiadis, George; Kalogeras, Konstantine; Tsiptsios, Iakovos; Tarlatzis, Basil; Fountzilas, George
Abstract Background Paclitaxel-based regimens are frequently associated with the development of peripheral neuropathy. The autonomous nervous system (ANS) effects, however, of this chemotherapeutic agent remain unexplored. Methods We investigated a group of 31 female patients with ovarian cancer receiving treatment with paclitaxel and carboplatin, as well as a group of 16 healthy age- and gender-matched healthy volunteers. All study participants completed a questionnaire and were assessed neurophysiologically at three time points (baseline, 3–4 months and 6–8 months following the onset of chemotherapy). The evaluation of the ANS included assessment of the adrenergic cardiovascular function (orthostatic hypotension-OH), parasympathetic heart innervation (30/15 ratio) and sympathetic skin response (SSR). Results At the 3–4 months ANS assessment, 19.2 % of the patients had systolic OH and the same percentage had diastolic OH, but at the 6–8 months evaluation no patient had systolic OH and only 13.8 % had diastolic OH. The values of the 30/15 ratio were significantly reduced at both time points, whereas the SSR was not affected. Conclusions Combined paclitaxel and carboplatin chemotherapy is associated with significant effects on the parasympathetic heart innervation and occasionally with effects on the adrenergic cardiovascular reaction. The SSR remained unaffected. Physicians should be alert to the possibility of these treatment-emergent side effects, so as to monitor ANS parameters and introduce treatment modifications accordingly. Our findings however, should be validated in larger cohorts.